Mewujudkan Keadilan dalam Pembagian Harta Waris Menurut Hukum Islam - Bintang, Putri Mutiara; Jauharah, Atha Nuraini; Dewi, Kaia Callysta; Rofiq, Nur (Ngaji: Jurnal Pendidikan Islam, 2024)
As one of the important aspects of Islamic law, the division of inheritance has been regulated in Islam in detail and in accordance with the principles of justice. Mistakes in the division of inheritance risk causing disputes and quarrels. So it is important to learn the science of inheritance distribution so that the implementation and distribution are fair to all parties. The writing of this journal aims to find out for whom and how the fair distribution of inheritance is carried out. This journal uses library research methods sourced from scientific journals, also sourced from Al-Quran, Surah An-Nisa: 11-12 which are the main source to get an understanding and explanation of the division of inheritance. It is concluded in this journal that the distribution of inherited property has been determined for whom the inheritance is given and how much the share is and the conditions for getting it.   Abstrak: Sebagai salah satu aspek penting dalam hukum islam, pembagian harta warisan sudah diatur dalam agama islam secara rinci dan sesuai dengan prinsip keadilan. Kesalahan dalam pembagian harta warisan beresiko menimbulkan perselisihan dan pertengkaran. Sehingga penting untuk mempelajari ilmu pembagian warisan agar dalam pelaksanaan dan pembagiannya adil bagi semua pihak. Penulisan jurnal ini bertujuan mengetahui untuk siapa dan bagaimana pembagian warisan yang adil dilakukan. Jurnal ini menggunakan metode penelitian pustaka yang bersumber pada jurnal-jurnal ilmiah, juga bersumber pada kitab Al-Quran yaitu surat An-Nisa ayat 11-12 yang menjadi sumber utama untuk mendapatkan pemahaman dan penjelasan tentang pembagian harta warisan. Disimpulkan dalam jurnal ini bahwa pembagian harta warisan sudah ditetapkan untuk siapa warisan diberikan dan berapa besar bagiannya serta syarat-syarat untuk mendapatkannya. Kata Kunci: Hukum Islam, Warisan, Ahli Waris, Pewaris, Wasiat, Tirkah